Hemophilia A. Considerations for dental management of pediatric patients. - Sonia López-Villareal; Osvelia Rodríguez-Luis; Norma Cruz-Fierro (Universidad de Concepción., 2016)
It comes to consulting the Faculty of Dentistry at the University of Nuevo León pediatric male patient of 9 years 10 months, who was admitted with a presumptive diagnosis of hemophilia due to a subsequent persistent bleeding to treatment with steel crowns made in an earlier appointment. Interconsultation is performed with the hematologist who by laboratory examinations notice decreased coagulation factor VIII confirming the diagnosis of hemophilia A. It plans and conducts comprehensive treatment dental team with the hematologist who said that patients in hospitals with the replacement of missing clotting factor is prepared by cryo precipitates or with concentrated factor VIII intravenously before and after his dental intervention. The aim of the article is to highlight that hemophilia can be a disease detected during dental surgery in some patients and for it to be successfully treated with multidisciplinary management protocol is required between hematologists and dentists.